RaitaSnehi - A Voice Based Farmer Information System - Malage, Gourish; Patil, Kiran Kumari (International Journal of Computer Sciences and Engineering, 2019)
India is a nation with more than half of its citizens dependent on agriculture for its survival, but only uses 14 percent of its GDP contribution. The nation has divided portions of land, resulting in a significant number of individual farmers with a nearly stagnant productivity. Despite government actions at both the center and the state level, a gap between land and lab our continues. With over 80% of the entire land holdings of tiny and marginal landowners, Karnataka is no exception. The search engine researchers have focused their efforts for years and years on having search engines that are more accurate and faster. In the past, this was more than enough, But the concept of getting everything intelligent became with smart phone appearance. In this paper we attempted to implement a proposed model of a voice-based farmer information system called ("RaitaSnehi") that provides data on the various schemes that farmers can get from various websites. Based on choices that farmers need to know, the user is prompted to give voice input. The word recognition algorithm is then applied using the Python environment and the recognized word is searched from the website in the parsed data and the details of the required data are read out on demand to the farmer. The word recognition algorithm is implemented, which is the template-based comparative algorithm based on hidden markov model, and the results are checked for accuracy. The words are given in the language of Kannada and the results are obtained in the language of Kannada to make the farmers comfortable. Python translation tool is used to convert English to Kannada and when reading from web sources, these words are converted to text to voice in Kannada Language. Through the document we will explain each portion of the proposed model in detail.